Antioxidant phenolic compounds from Chinese white olive (Canarium album L.) - Xiang, Zhaobao; Wu, Xiaoling; Liu, Xingyu; Chen, Gang (Bangladesh Journal of Botany, 2020)
To find antioxidant compounds from Chinese white olive (CWO) based on bioassay-guided method, the ethanol extract and corresponding 4 fractions were evaluated for their antioxidant activities by DPPH and ABTS assay. The results revealed that the AcOEt fraction had the most potent antioxidant activity. Further, six compounds isolated from the AcOEt fraction, and their structure were identified as (-)-epicatechin gallate (i), ellagic acid (ii), gallic acid (iii), (-)-epigallocatechin (iv), (-)-epigallocatechin gallate (v) and kaempferol (VI) by MS and NMR spectrum. Compounds I, IV and V were isolated and identified from CWO for the first time. All the compounds (I-VI) exhibited potent antioxidant activity. Among them, compound III showed best antioxidant activity in both DPPH and ABTS+ assay. The phenolic compounds from CWO with potent antioxidant activities were responsible for the antioxidant activity of CWO extract.